2010
DOI: 10.1007/s00422-010-0376-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phase on homeostatic spike rates

Abstract: Recent experimental results by Talathi et al. (Neurosci Lett 455:145-149, 2009) showed a divergence in the spike rates of two types of population spike events, representing the putative activity of the excitatory and inhibitory neurons in the CA1 area of an animal model for temporal lobe epilepsy. The divergence in the spike rate was accompanied by a shift in the phase of oscillations between these spike rates leading to a spontaneous epileptic seizure. In this study, we propose a model of homeostatic synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Here significant enhancement is obtained throughout most the entire range of driving frequencies and the mean phase coherence increase is shifted towards higher frequencies ( Figure 12), with no activity ratio peaks at specific frequencies.This suggests that a mere change of balance between excitatory and inhibitory currents due to formation of additional synapses [53] or background spikes rates [47], cannot generate the same results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here significant enhancement is obtained throughout most the entire range of driving frequencies and the mean phase coherence increase is shifted towards higher frequencies ( Figure 12), with no activity ratio peaks at specific frequencies.This suggests that a mere change of balance between excitatory and inhibitory currents due to formation of additional synapses [53] or background spikes rates [47], cannot generate the same results.…”
Section: Discussionmentioning
confidence: 92%
“…At the same time it also allows the enhanced region for higher activity leading then to stronger inhibition and more thorough shutdown of other network regions 9A. Recent computational work by Fisher et al [47] has shown that target spiking rates can be achieved in networks with different balances of excitatory and inhibitory neurons. Such a system might also respond variably to different input frequencies, as our result suggests.…”
Section: Number Of Inhibitory Neuronsmentioning
confidence: 99%
“…For example, in biomedicine, vast electroencephalogram (EEG) or electrocorticogram (ECoG) data are available for the analysis, detection, and possibly prediction of epileptic seizures (e.g., Refs. [9][10][11][12][13][14][15][16]). In a modern infrastructure viewed as a complex dynamical system, large scale sensor networks can be deployed to measure a number of physical signals to monitor the behaviors of the system in continuous time [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments by our group in a chronic limbic epilepsy animal model have lead to the hypothesis that epilepsy following brain injury may emerge as a circadian disorder [1,2]. Specifically, we extracted two distinct classes of population spikes (PS) from CA1 local field potential data.…”
mentioning
confidence: 99%